REPRESENTASI FANATISME SUPPORTER DALAM FILM ROMEO DAN JULIET - Aditya Rizky Gunanto (Jurnal Visi Komunikasi, 2015)
Romeo and Juliet movie tells the story of love between two mutually hostile angggota supporters. Rangga as a staunch supporter of Persija FC, and Dessy as a staunch supporter of Arsenal FC In unite their love, Rangga and Dessy faced with a problem, so they decided to get married and plan to escape to a neutral city where their competition is not a problem. But brother Dessy not bend over backwards to stop it. A true love story of two people has been the biggest supporter of the affairs of the two organizations .The theory used in this study is the theory of semiotics by Charles Sanders Peirce. Semiotics is the study of signs, meanings and proper functioning of the production of meaning. Charles Sanders Peirce's theory of meaning called triangle (triangle of meaning), including signs, objects (reference mark), and interpretant (users sign) This type of research uses descriptive qualitative approach. Research methods with semiotic analysis that focuses on the meaning of each sign in the form of an icon, index, and symbol. The unit of analysis is a picture of a sign in the movie "Romeo Juliet". Research scope fanaticism of supporters who will be studied focusing on any scene that contains elements of fanaticism were analyzed through semotika Peirce. Film Romeo dan Juliet menceritakan tentang percintaan antara dua angggota supporter yang saling bermusuhan. Rangga sebagai pendukung setia Persija FC, dan Dessy sebagai pendukung setia Persib FC Dalam mempersatukan cinta mereka, Rangga dan Dessy dihadapkan pada suatu masalah, sehingga mereka memutuskan untuk menikah dan merencanakan untuk melarikan diri ke sebuah kota netral di mana persaingan mereka tidak masalah. Tapi kakak Dessy tidak sekuat tenaga untuk menghentikannya. Sebuah kisah cinta sejati dua orang telah menjadi urusan dua organisasi pendukung terbesar. Teori yang digunakan dalam penelitian ini adalah teori semiotika menurut Charles Sanders Peirce. Semiotika adalah ilmu yang mempelajari tentang tanda, berfungsinya makna dan produksi makna. Teori dari Charles Sanders Peirce disebut triangle meaning (segitiga makna), diantaranya tanda, objek ( acuan tanda), dan interpretant (pengguna tanda). Tipe penelitian ini menggunakan pendekatan kualitatif yang bersifat deskriptif. Metode penelitian dengan analisis semiotik yang memfokuskan pada makna masing-masing tanda baik berupa ikon, indeks, maupun symbol. Unit analisis ini berupa gambar dari sign dalam film “ Romeo Juliet”.Ruang lingkup penelitian fanatisme supporter yang akan diteliti memfokuskan pada setiap adegan yang mengandung unsur fanatisme yang dianalisis melaui semotika Peirce.